Development of Interactive Educational Videos to Improve Children's Math Skills in Kindergarten - Widiyawati; Nurhafizah; Rakimahwati; Dadan Suryana (Postgraduate, University of Mataram, 2026)
This study aimed to develop and analyze the validity, practicality, and effectiveness of Canva-based Interactive Educational Videos to improve the mathematical abilities of children aged 5–6 years in kindergarten learning. The novelty of this research lies in the integration of animated visualization, audio narration, interactive quizzes, and self-assessment features into a Canva-based numeracy learning media specifically designed for early childhood education using the ADDIE development model. This research employed the Research and Development (R&D) method with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 20 children aged 5–6 years in Group B at Humhaz Kindergarten, West Pasaman, Indonesia. Data were collected through observation, interviews, questionnaires, documentation, and pretest-posttest tests, then analyzed using descriptive statistics and N-Gain analysis. The results showed that the developed media obtained a validity score of 93.3% from material experts and 95.8% from media experts, both categorized as very valid. The practicality test results reached 95% in the small-group trial and 100% in the large-group trial, indicating that the media were very practical and easy to implement in classroom learning. Furthermore, the average score increased from 19.15 in the pretest to 25.1 in the posttest, with an N-Gain value of 0.5350 categorized as moderate improvement, indicating that the media were sufficiently effective in improving children’s mathematical abilities. However, this study was limited to one kindergarten with a relatively small sample size and short implementation duration. Practically, the developed media can be applied by PAUD/TK teachers as an interactive digital learning medium to support numeracy instruction through projector- or device-assisted classroom activities that are more engaging and developmentally appropriate for early childhood learners.